Book reviewed: Cultura del juicio y experiencia del arte. Ensayos. Autor: Javier Domínguez - Rojas Osorio, Carlos (Estudios de Filosofía, 2003)
Book reviewed: Cultura del juicio y experiencia del arte. Ensayos. Autor: Javier Domínguez